Financial Sector Assessment Program Update : Egypt - World Bank (Washington, DC, 2013)
A joint team from the International Monetary Fund's (IMF's) Monetary and Financial Systems Department (MFD) and the World Bank visited Egypt between May 6 and May 21, 2007 to update the assessment of the Egyptian Financial Sector Assessment Program (FSAP) that had been conducted in June 2002 and completed in September 2002. The work under the FSAP update aimed to assess progress in reforming the financial sector and strengthening financial sector regulation since 2002, and identify measures that will contribute to the consolidation of the financial sector reform and the further development of the financial sector over the next five years.